PENGGUNAAN TEKNOLOGI DALAM DETEKSI DAN PENCEGAHAN PERDAGANGAN ORANG: PELUANG DAN TANTANGAN - Idul Adnan; Muh. Rizal Hamdi; Lalu Hendri Nuriskandar (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
Human trafficking remains a grave violation of human rights, and its complex nature necessitates innovative approaches for effective detection and prevention. This study explores the role of technology in combating human trafficking, highlighting both the opportunities and challenges associated with its implementation. Advanced technologies such as machine learning algorithms, big data analytics, and blockchain are utilized to monitor suspicious activities, identify trafficking patterns, and ensure transparency in supply chains. Moreover, digital platforms and mobile applications provide crucial support for victims by enabling anonymous reporting and access to emergency assistance. Despite these advancements, significant challenges persist, including data privacy and security concerns. This research emphasizes the need for robust policies and collaborative efforts between public and private sectors to develop secure and effective technological solutions in the fight against human trafficking.